On the anatomy and topography of the pancreas and the pancreatic duct in reindeer {Rangifer tarandus tarandus L) - Sven Nikander (Rangifer, 1990)
The complex development of the pancreas accounts for the differences in its morphology among various animal species. According to the present study, the anatomy of the pancreas in the reindeer is quite similar to that in small ruminants. It consists of two lobes, the left one (tail) extending in a ventrodorsal direction is in contact with the rumen, spleen, and the left adrenal gland. The right lobe (head) lies within the curve of the duodenum. Ducts analogous to the ductus pancreaticus major (Wirsungi) and minor (Santorini) join in a common pancreatic duct (ductus pancreaticus) which opens into the common bile duct (ductus hepaticus communis). Haiman ja haimakäytävän anatomia ja topografia porolla. Abstract in Finnish / Yhteenveto: Haiman kehittyminen on monimutkaista, mikä aiheuttaa sen, että haiman rakenne vaihtelee eri eläinlajeilla. Tämän tutkimuksen mukaan haiman rakenne porolla on hyvin samanlainen kuin pienillä märehtijöillä. Haimassa on kaksi lohkoa. Vasen lohko (häntä) on ventrodorsaalisessa suunnassa ja koskettaa pöt-siä, pernaa ja vasenta lisämunuaista. Oikea lohko (pää) sijaitsee pohjukaissuolen mutkassa. Ductus pancreaticus majoria (Wirsungi) ja minoria (Santorini) vastaavat haimakäytävät yhtyvät muodostaen ductus pancreaticuk-sen, joka avautuu yhteiseen sappikäytävään (ductus hepaticus communis). Pankreas och ductus pancreaticus anatomi och topografi hos ren. Abstract in Swedish / Sammandrag: Pankreas ontogenes är invecklad, detta medför morfologiska variationer hos de olika djurarterna. Enligt denna undersokning påminner pankreas anatomi hos renen om de små idisslarnas. Pankreas består av två lober. Den vänstra loben (svansen) stracker sig i ventrodorsal riktning och gränsar till våmmen, mjälten och den vänstra binjuren. Den högra loben (huvudet) år i en slinga av tolvfingertarmen. Analoga gångar till ducuts pancreaticus major (Wirsungi) och minor (Santorini) förenas till ductus pancreaticus som mynnar ut i gallgången (ductus hepaticus communis).